Application of business process re-engineering in a company in Singapore - Chan, Kam Piew (2013)
In this region, many top managers perceive Business Process Reengineering (BPR) as no more than the latest in a long line of management fads. According to a local consultant, they respond to this idea with cynicism because they see BPR as simply a new name for total quality management. At the same time, they are desperate for new paradigms because they are afraid of not being able to change their organisations fast enough to cope with the tremendous growth in this Far East region.